Consent issue and determination of a girl`s age in Malaysian statutory rape law: an analysis from shariah perspective - Abdullah, Nur Aina; Haneef, Sayed Sikandar Shah (Usuli Faqih Research Centre PLT, 2018)
The statutory rape under section 375 (g) of the Malaysian Penal Code refers to the intercourse of a man with a woman under the age of 16 either by the consent of the woman or without her consent. It is also known as underage rape where the element of the woman's consent is considered immaterial in law. However, based on the statistics and reports obtained from the Royal Malaysian Police (PDRM), the vast majority of these statutory rape cases are voluntary and consensual sexual intercourse between teenage couples, supposedly based on love. In fact, according to reports, the age limit of adolescent girls involved in this voluntary sex activity is around 13 to 15 years old, with a majority of whom are Muslim. Hence, it raises questions that need to be considered from the Shariah point of view. This paper aims to examine the consent issue (concept of willingness) and the age limit of adolescent girls contained in statutory rape laws from a perspective of Shariah perspective. A qualitative approach with content analysis study design is used as a methodology of this study. Secondary data that is the law and classical and contemporary Fiqh law has been used in the collection of research data. It is also supported by statistical data obtained directly from interviews with PDRM officers. The data were analyzed thematic and assisted by Atlas.ti software as facilitator tool. The findings show that consent issue and age limits of the girls in statutory rape laws in Malaysia are less relevant to today's developments, even less in accordance with Shariah principles. Therefore, proposals are proposed to harmonize this statutory rape law with Shariah principles for the sake of well-being and to preserve the dignity of women and to care for the offspring (hifz al-nasl).